Women as Agents of Change: Exploring Women Leaders’ Resistance and Shaping of Gender Ideologies in Pakistan - Chaudhary, Nabiha; Dutt, Anjali (Frontiers in Psychology, 2022)
Despite a growing focus on processes to promote gender equity, women remain significantly underrepresented in leadership positions in the Global South. In the present study we focus on the role of familial experiences in shaping and contesting gender ideologies of Pakistani women in the workplace. We specifically examine the reciprocal ways in which women leaders and their family members shape each other’s gender ideologies regarding the workplace. Qualitative data were collected via semi-structured interviews with sixteen participants in Lahore, Pakistan: eight women in positions of leadership and eight family members of the women leaders (one family member each). Using thematic narrative analysis, we identified three thematic phases: learning gender expectations, resistance, and familial transformation. These phases reflect the progression of developing, resisting, and influencing individual and familial gender ideologies. We document the manifestation of these phases in three specific domains: education, marriage and motherhood, and the workplace. We then discuss how these findings contribute to understanding the context-specific experiences of women leaders and perceptions of their family members regarding women’s role in the workplace. Findings from our research provide novel insights into the ways globalization and capitalism continue to shape the socio-cultural context for women leaders in the Global South.